'A Jolly Romp We Were Always Destined to Win': The BBC's 'Allo 'Allo! and British Memories of Downed Aircrew in Occupied France during the Second World War. (12th April 2016) - DEACON, VALERIE
Abstract: The long-running BBC sitcom, 'Allo 'Allo!, has been thoroughly criticised for its use of various racial, gendered and sexualised tropes, not to mention its cynical view of the French experience of the Second World War. This article, however, reassesses the programme in light of what it highlights about the lived experience of Anglo-American airmen who were forced to bale from their planes over Occupied France. It uses the comedic aspects of the programme to investigate escape and evasion training, the use of language, 'fitting in' and the prominence of peasants in the wartime lives of Anglo-American aircrews in France. The programme, rather than being just another example of Gaullophobia, accurately represents some elements of the Second World War in France. In addition, changes in the plot over its nine seasons suggest that the sitcom reflects broader British concerns, as well as the Anglo-French relationship.